Complaint Handling Management System (CHMS) Application in Increasing Customer Satisfaction at PT Bank Syariah Indonesia TBK - Mulida, Mulida; A Sabil, Rozi; Maju Simatupang, Batara; Haryanti, Enny (Dinasti Publisher, 2025)
This study is motivated by the increase in customer complaints at BSI from 2021 to 2023, despite a reduction in SLA for complaint resolution. The purpose of this study is to analyze the implementation of the Complaint Handling Management System (CHMS) in handling customer complaints at PT Bank Syariah Indonesia Tbk (BSI) and to identify potential bottlenecks as well as customer satisfaction with the complaints process. This research uses a qualitative method with a descriptive approach. The subjects of this study include BSI employees managing the CHMS and customers who use the complaint service. The results show that the CHMS application successfully reduced the SLA for complaints, from 8.45% to 0.71%, indicating improved speed and efficiency of handling complaints. However, bottlenecks were still identified. Overall, customer satisfaction with the CHMS application is high, with 82.79% of customers expressing satisfaction with the service. The implications of this study suggest the importance of continually enhancing employee training and optimizing the automation features within CHMS to reduce bottlenecks and further improve customer satisfaction.